4-[(2-Chloroethyl)amino]quinolinium chloride monohydrate - James L. Wardell (Acta Crystallographica Section E, 2009)
In the title salt hydrate, C11H12ClN2+·Cl−·H2O, the quinolinium core is essentially planar (r.m.s. deviation = 0.027 Å) with the chloroethyl side chain being almost orthogonal to the core [C—N—C—C torsion angle = −80.0 (3)°]. In the crystal packing, the water molecule bridges three species, forming donor interactions to two chloride anions and accepting a hydrogen bond from the quinolinium H atom. The chloride anion accepts a hydrogen bond from the amine N atom with the result that a two-dimensional supramolecular array is formed in the ac plane. A C—H...Cl interaction also occurs.